2010
DOI: 10.1155/2010/246492
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Access to GastroEnterology in Canada: The SAGE Wait Times Program

Abstract: Median wait times for gastroenterology services continue to exceed consensus conference recommended targets and have significantly worsened since 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 7 publications
1
32
0
2
Order By: Relevance
“…Even without a (colonoscopy) screening program, several countries already have a waiting list for colonoscopy, with waiting times of more than 6 months reported (63–65). Implementing a guaiac FOBT screening pilot has been shown to increase colonoscopy activity by 21%–31% (66).…”
Section: Discussionmentioning
confidence: 99%
“…Even without a (colonoscopy) screening program, several countries already have a waiting list for colonoscopy, with waiting times of more than 6 months reported (63–65). Implementing a guaiac FOBT screening pilot has been shown to increase colonoscopy activity by 21%–31% (66).…”
Section: Discussionmentioning
confidence: 99%
“…In 2008, the Survey of Access to Gastroenterology in Canada (SAGE) study analyzed whether these consensus targets were being met. This study identified two types of wait lists central to GI: one for specialist consultation and one for diagnostic procedures (5). It was concluded that both wait lists were longer than published consensus targets, and this was also demonstrated in other studies (5)(6)(7)(8).…”
mentioning
confidence: 53%
“…In the pediatric population, patients are not referred for endoscopy for screening purposes, but rather because they are symptomatic. Thus, it seems reasonable that wait times in pediatric GI should be shorter than adult wait times (5). The SAGE study compared its results with the consensus targets established in 2005 and concluded that these targets were not being met in adult GI.…”
Section: Discussionmentioning
confidence: 99%
“…Direct to colonoscopy, also referred to as “open access colonoscopy”, allows for provision of a colonoscopy without clinical consultation with the endoscopist prior to the day of the procedure. In an era of lengthy consultation waitlists and limited clinic resources[2], this pathway has potential to facilitate expedited clinical care for many patients. Timely access is critical because delays in diagnostic colonoscopy may result in significant delays in cancer diagnosis[3,4].…”
Section: Introductionmentioning
confidence: 99%